The Indian Role and the Future ofRelations of Power in Asia in 21 Century - Belharbi, Oumar (Milev Journal of Research and Studies, 2021)
India seems as one of the dynamic powers in power relations in the Twenty First century, which qualifies it to play a role in making the future of the world powers, as it coincides with the constant economic growth, so India is classified as the second power at global level, in terms of growth after China, however, this development has witnessed several periods until now, as socialism and central planning have been adopted ineconomic field, despite the fact it is a democratic State, which makes it unique within the socialist camp, therefore, it was easy for it to introduce large reforms in the beginning of 1990s, making it a big start and it helped to achieve a significant economic growth, besides, a shift into sophisticated technology, which has been concomitant with the growing regional role of India, and it will qualify it to play a key global role in the future of powers in the South Asia and South-East Asia in the short and long.